Maternal feeding practice and its relationship with stunting in children - Prihatini Dini Novitasari; Dessie Wanda (MDPI AG, 2020)
The incidence of stunting in children is a crucial problem that remains challenging to tackle and is caused by multiple factors. This study aimed to determine the relationship between maternal feeding practice and the incidence of stunting in children in Depok, Indonesia. The study design was a correlation analysis with a cross-sectional approach including applied height-for-age z-score tables from the World Health Organization (WHO) and a feeding practices and structure questionnaire (FPSQ- 28). The study involved 262 participants who were selected using a cluster random sampling technique in 11 district health centers in Depok. The results suggest that there was no significant relationship between maternal feeding practice and the incidence of stunting in children in Depok (P>0.05). In addition, feeding practice performed by mothers was rather non-responsive. The study results are expected to provide benefits for nurses and health professionals in order to improve health education and promotion programs related to stunting and responsive feeding practice.